PENGARUH BERAT LAHIR MENURUT USIA KEHAMILAN TERHADAP KELANGSUNGAN HIDUP BAYI DI INDONESIA - Lisa, Mona; Arriawan, Iwan; Besral, Besral; Pratomo, Hadi; Hermawan, Lukas C; Tarigan, Ingan Ukur (Universitas Mohammad Husni Thamrin, 2023)
Infant survival is defined as the ability of infants to survive through life until the age of 1 year. In 2012, Indonesia IMR reportedd as 32 per 1,000 live births. Sosio economic status will affect infant survival through maternal factors, nutrition, fetal condition at birth, disease control and environment. This study aims to determine the effect of birth weight for gestational age on the infantâ€™s survival in Indonesia. The Method of study is a retrospective cohort, utilize of data 13 295 child data contained in the Riskesdas data 2013. Result of the analysis showed that the survival of small for gestational age had the lowest probability of 97%. Results cox regression showed that small for gestational age on the high economic status, HR = 8.95, the middle-income status, HR = 3.72, and the poor economic status, HR = 7.36. Small for gestational age have contributed to infant mortality in the population by 42%. Improving the quality of antenatal care for during pregnancy and socialization of kangaroo care method for birth weight small for gestational age is an alternative to decrease the incidence of small for gestational age.Â Keywords:Â infant survival, small for gestational age, economic status